Veggies and Herbs Made in the Shade: A Growing Season Calendar for North Florida - Daniel K. Fenneman; Robert C. Hochmuth; Wanda L. Laughlin; Sean R. McCoy (EDIS, 2014)
The importance of using an open shade structure for hydroponic crop culture in Florida has recently increased. Prior to the turn of the century, hydroponic culture in Florida was done inside a greenhouse structure, but it has now expanded to several other types of structures. In addition to greenhouses, production now exists in high tunnels, insect screens or net houses, and open shade-covered structures. In southern parts of Florida, outdoor hydroponic systems without any structure are becoming more common. In those cases, many operations use a polypropylene cover for freeze protection. Diversifying structures stems from growers’ desires to extend the season to meet consumer demand for a longer time period. The purpose of this publication is to indicate what crops have been successfully grown under shade in northern Florida at various times of the year. This 4-page fact sheet was written by Daniel K. Fenneman, Robert C. Hochmuth, Wanda L. Laughlin, and Sean R. McCoy, and published by the UF Department of Horticultural Sciences, November 2013.